EFEITOS DE FONTES E DOSES DE SELÊNIO NA PRODUTIVIDADE E QUALIDADE DE GRÃOS DE FEIJÃO - (:unkn) unknown (Universidade Estadual de Goiás, 2023)
Beans (Phaseolus vulgaris) are cultivated practically all over the world and have great importance for the population in economic and cultural aspects. Due to increasing population expansion, increased occurrences of abiotic and biotic stresses, it is necessary to develop new production technologies. Biofortification with Se in bean culture is a strategy that can solve problems in human nutrition. The objective of this work was to evaluate the effect of sources and doses of selenium via the leaves in the bean crop. The study was conducted in Campo Alegre De Goiás – GO. The experiment was set up in a randomized block experimental design in a 2x5 factorial scheme, with four replications, totaling 48 experimental plots. The first factor refers to two sources of selenium (sodium selenate –Na2SeO4 and sodium selenite – Na2SeO3). The second factor is selenium doses (0; 100; 200; 300; 400 and 500 g ha-1 ). Data regarding plant height, toxicity levels, productivity, sieve classification, average seed weight, number of pods and seeds per plant, seed viability test and selenium content in the grain were evaluated. Although the results did not present a significant difference between the treatments regarding the number of grains per plant, number of pods and number of grains per pod. The application of Na2SeO4 at a dose of 250 g ha-1 showed better results regarding productivity. The application of both Na2SeO4 and Na2SeO3 provided a reduction in the height of bean plants and also showed symptoms of phytotoxicity, being more intense in the source of Na2SeO3. The best result regarding seed viability in the first seed count was at the dose of 330 g ha-1 . It was possible to increase the Se content in beans using both Na2SeO4 and Na2SeO3 in foliar fertilization. Agronomic biofortification with Se in beans is best achieved at a dose of 414 g ha-1 when using Se in the form of Na2SeO4, however it is not the ideal dose for the recommended daily intake.
EFFECTS OF SOURCES AND DOSES OF SELENIUM ON THE PRODUCTIVITY AND QUALITY OF BEAN GRAINS
Keywords: Phaseolus vulgaris; Selenato de Sódio; Selenito de Sódio.; Sodium Selenate; Sodium Selenite; AGRONOMIA::CIENCIA DO SOLO